Tobacco and alcohol usage as risk factors of non-communicable diseases among students of Zenica University (Bosnia and Herzegovina) - Adnan Mujezinović; Lejla Čalkić; Nino Hasanica; Salih Tandir (Medicinski glasnik, 2018)
Aim To establish the presence of two risk factors, smoking and alcohol use, for non-communicable diseases among students at the University of Zenica. Methods The research was conducted at eight schools of the University of Zenica in the academic year 2016/2017 during the period from 1 December 2016 to 15 February 2017. The study involved 600 students 19-29 years of age (all years of study). The research was carried out with a standardized and validated questionnaire, the STEPS non-communicable Disease Risk Factors survey, developed by the World Health Organization. Results Tobacco was used by 145 (24.2%) students, 68 (46.9%) of them being males and 77 (53.1%) females (p<0.05). Males smoked 15.62 and females 13 cigarettes per day (p<0.05). On average, male participants were 16.56 years old, and female participants 16.71 when they started consuming cigarettes (p<0.05). A total of 289 (48.1%) students consumed alcohol, of whom 135 (70.2%) were males and 154 (37.7%) females (p<0.05). Conclusion There is evidence of high prevalence of smoking and alcohol usage as the risk factors for non-communicable diseases. Two levels of the prevention measures should be applied in order to reduce the prevalence of such risk factors: strategic level with a definition of the population, actors, activities, target population and anticipated results, and tactic level which will show contingency activities at the University.
Keywords: smoking; alcohol drinking; prevalence